2008
DOI: 10.1007/s11120-008-9386-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorylation on the thermal and light stability of the thylakoid membranes

Abstract: Higher plant thylakoid membranes contain a protein kinase that phosphorylates certain threonine residues of light-harvesting complex II (LHCII), the main light-harvesting antenna complexes of photosystem II (PSII) and some other phosphoproteins (Allen, Biochim Biophys Acta 1098: 275, 1992). While it has been established that phosphorylation induces a conformational change of LHCII and also brings about changes in the lateral organization of the thylakoid membrane, it is not clear how phosphorylation affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…A similar structure was previously observed as a native form of LHCII in thylakoid membranes (21). The structural alteration conferred by LHCII phosphorylation (11,(22)(23)(24) could cause these aggregations. Furthermore, FLIM and spectroscopic measurements indicated that the phospho-LHCII was energy-dissipative as compared with unphosphorylated LHCII (Fig.…”
Section: Chlorophyll Fluorescence Lifetime Of Dissociated Phospho-lhcsupporting
confidence: 76%
“…A similar structure was previously observed as a native form of LHCII in thylakoid membranes (21). The structural alteration conferred by LHCII phosphorylation (11,(22)(23)(24) could cause these aggregations. Furthermore, FLIM and spectroscopic measurements indicated that the phospho-LHCII was energy-dissipative as compared with unphosphorylated LHCII (Fig.…”
Section: Chlorophyll Fluorescence Lifetime Of Dissociated Phospho-lhcsupporting
confidence: 76%
“…The molecular mechanism of LHCIIb to regulate its different functions is realised via changes in the macro-molecular structures in the membrane and the phosphorylation-dephosphorylation of LHCIIb (Allen 2005b;Horton et al 2008). This multi-functional characteristic ensures highly efficient light harvesting and sensibility against the situations of over-excitation (Bassi and Caffarri 2000;Szabo et al 2008;Varkonyi et al 2009). …”
Section: Sensing the Change-variation In Photosynthetic Function Medimentioning
confidence: 99%
“…In case of the unbalanced functioning of PSII and PSI a redox-controlled energy redistribution occurs between the two photosystems, a process known as state transition, during which large structural reorganizations have been shown to occur (Allen 2003;Allen and Forsberg 2001;Chuartzman et al 2008;Iwai et al 2010;Rochaix 2007;Várkonyi et al 2009). In plants exposed to excess light, associated with the non-photochemical quenching of the chlorophyll singlet excited state, substantial reorganizations have been observed (Barzda et al 1996;Dall'Osto et al 2005;Grudziński et al 2002;Gruszecki et al 2006;Horton et al 2008;Horton et al 1996;Istokovics et al 1997;Lambrev et al 2007a).…”
Section: Introductionmentioning
confidence: 99%